2021
DOI: 10.1002/chem.202004672
|View full text |Cite
|
Sign up to set email alerts
|

Polyvalent Transition‐State Analogues of Sialyl Substrates Strongly Inhibit Bacterial Sialidases**

Abstract: Supporting information for this article is available.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 51 publications
(106 reference statements)
0
18
0
Order By: Relevance
“…over the 33 reactive groups present in 3) were conjugated to 3 by CuAAC, with tris(benzyltriazolylmethyl)amine (TBTA), L-sodium ascorbate and CuSO 4 in PBS similarly to previous reports. [26,27,28] After 24 h at room temperature, the resulting homovalent neoGPs 4 a-c were purified on Sephadex G25. The purity was confirmed by SDS-PAGE and MALDI-TOF experiments enabled to estimate that between 12 to 19 tetravalent glycodendrons were coupled to BSA, which corresponds to 49-75 glycans per BSA and molecular weights from 92 to 105 kDa for homovalent neoGPs 4 a-c (Table 1, FigureS11 and S14).…”
Section: Synthesis Of Neogpsmentioning
confidence: 99%
See 3 more Smart Citations
“…over the 33 reactive groups present in 3) were conjugated to 3 by CuAAC, with tris(benzyltriazolylmethyl)amine (TBTA), L-sodium ascorbate and CuSO 4 in PBS similarly to previous reports. [26,27,28] After 24 h at room temperature, the resulting homovalent neoGPs 4 a-c were purified on Sephadex G25. The purity was confirmed by SDS-PAGE and MALDI-TOF experiments enabled to estimate that between 12 to 19 tetravalent glycodendrons were coupled to BSA, which corresponds to 49-75 glycans per BSA and molecular weights from 92 to 105 kDa for homovalent neoGPs 4 a-c (Table 1, FigureS11 and S14).…”
Section: Synthesis Of Neogpsmentioning
confidence: 99%
“…The binding ability of the homovalent neoGPs 4 a-c was studied with LecA and LecB using the GLYcoPROFILE® technology (GLYcoDiag, France). [26,27,28,31] NeoGPs 4 a-c were first labelled with biotin using the protocol described previously then were incubated in microtitration plates coated with lectins. Streptavidin labelled with 5-(4,6-dichlorotriazinyl)-aminofluorescein (DTAF) was finally incubated in each well and the interaction was directly detected by reading the fluorescence intensity (FI) provided by the neoGP bound to the lectin.…”
Section: Direct Binding Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it was shown that the binding modes of Jack Bean α-mannosidases with iminosugar-based multivalent inhibitors not only depend on the nature and number of bioactive inhitopes, but more importantly on the shape and size of the multivalent scaffold as well as ligand density [ 15 , 16 , 17 , 18 , 19 , 20 ]. Multimerization of inhitopes proved to be an attractive strategy, enabling valency-corrected inhibition enhancements of up to three [ 26 ] to four [ 27 ] orders of magnitude, inhibition selectivity refining or enzyme activation [ 28 , 29 ]. Multivalent drugs on nanoparticles also proved efficient for escaping efflux pumps [ 30 ].…”
Section: Introductionmentioning
confidence: 99%